Four new species of Phytobia Lioy (Diptera: Agromyzidae) from the Brazilian Amazon, with an updated key to the Neotropical species - Carvalho-Filho, Fernando S.; Cabá, Emiliano N.; Monteiro, Nilton J. S.; De-Souza, Caroline C. (Zootaxa, 2025)
Four new species of Phytobia Lioy (Diptera: Agromyzidae) are described based on specimens collected in four localities from the Brazilian Amazon: P. espositae sp. nov., P. munduruku sp. nov., P. piscivora sp. nov., and P. pium sp. nov. Figures of male terminalia and photographs of type specimens are presented. In addition, P. setitibialis Sasakawa and P. pluviasilvae Boucher are newly recorded from Brazil and P. megapodema Sousa & Couri is newly recorded for the Brazilian state of Acre. In addition, an updated key to the Neotropical Phytobia species is presented.